Repeat and Recall (R&R): memory booster handbook for students / Nor Azira Ayob, Mohd Amar Aziz and Noor Hadzlida Ayob - Ayob, Nor Azira; Aziz, Mohd Amar; Ayob, Noor Hadzlida (2023)
Memory is the most important factor in distinguishing from one person to the other. Memory is the ability to record information and remember what we see and learn. There are three basic types of memory that allow the brain to encode, store, and retrieve information. Without the three basic types of memory, an individual is unable to build personal rapport in order to acquire new knowledge and will be unable to perform basic functions in daily life such as studying. A good memory is dependent on the brain health and vitality. As a student, studying for a quiz or final exam necessitates greater effort, particularly in remembering the points, explanations, data, numbers, formulas. The Repeat and Recall (R&R): Memory Booster for Malaysian Economy Students is introduced to help students especially to study the subject of Malaysian Economy. Repeat and Recall (R&R): Memory Booster Handbook can provide the information needed by students with many simple words that can be easily understood. This memory booster is also suitable for all students, user friendly, handy and also easy to be carried anywhere. Simple pilot test interviews and survey were conducted for 30 students before and after using the R&R Memory Booster and the findings show that students are more aware of the concept after using this memory booster. Therefore, these memory boosters can help students to succeed and achieve better results.